2011
DOI: 10.1177/0960327111424302
|View full text |Cite
|
Sign up to set email alerts
|

Organic anion transporter 1 (OAT1) involved in renal cell transport of aristolochic acid I

Abstract: Aristolochic acids (AAs) are a family of structurally related nitrophenanthrene carboxylic acids that are present in medicinal herbs such as Aristolochia species. The organic anion transporters (OATs) of the solute carrier (SLC22) gene family located in the renal proximal tubules play a key role in the excretion of a variety of exogenous and endogenous compounds. However, it is unclear how AAs permeate into renal epithelial cells. In this regard, we investigated the role of rat OAT1 ([rOAT1] SLC22A6) in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…In addition, various other competition studies conducted in in vitro heterologous expression systems, also evaluated the interaction between AAI and OAT. It appeared that AAI is a high-affinity substrate for human and mouse OAT1 and OAT3 [77,86,91,95,96] but showed weak affinity for the human OAT4 [91]. These results suggest that the influx of AAI in PTEC through OAT1 and OAT3 is more important than their efflux through OAT4.…”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, various other competition studies conducted in in vitro heterologous expression systems, also evaluated the interaction between AAI and OAT. It appeared that AAI is a high-affinity substrate for human and mouse OAT1 and OAT3 [77,86,91,95,96] but showed weak affinity for the human OAT4 [91]. These results suggest that the influx of AAI in PTEC through OAT1 and OAT3 is more important than their efflux through OAT4.…”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
“…Only a few in vivo studies addressing AA transport in PTEC have been described in the literature [95,96,97]. In AA-treated mice, probenecid treatment has been found to decrease the renal distribution and the urinary excretion of AAI [95] but also to reduce tubular necrosis, lymphocytic infiltrate, tubular atrophy as well as fibrosis by blocking AA entry into PTEC as attested by the reduction of DNA-adducts formation [97].…”
Section: Properties Of Aa and Mechanisms Of Nephrotoxicity And Carmentioning
confidence: 99%
“…However, 90% of urate reabsorption is obtained through renal URAT1. Moreover, renal organic anion transporter 1 (OAT1) localized in the basolateral membrane and ATP-binding cassette transporter G2 (ABCG2) located at the apical membrane have been identified as main secretory urate transporters 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also found that AAI was a substrate of organic anion transporter 1 (OAT1) and OAT3, and renal OATs mediated the renal accumulation and renal toxicity of AAI. When inhibiting renal OATs, renal accumulation as well as renal toxicity of AAI would reduce (Xue et al, 2011;Zeng et al, 2012). However, few study cares for the AAI transport by intestinal efflux transporters.…”
Section: Introductionmentioning
confidence: 99%